Pengaruh User Generated Content, Brand Image, dan Hedonic Value terhadap Minat Pembelian pada Produk Salted Egg Milea: The Influence of User Generated Content, Brand Image, and Hedonic Value on Purchase Interest in Salted Egg Milea Products - Lawrence, Lucas; Rochefort, Thomas; Alwiyah, Alwiyah; Millah, Shofiyul (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2024)
This study aims to examine the influence of three main factors, User Generated Content (UGC), Brand Image, and Hedonic Value on consumer Purchase Intention towards Salted Egg Milea products. In today's digital era, the use of social media has become one of the main tools in product marketing. UGC is content created by users to recommend or reflect experiences with certain products, increasingly becoming a concern in marketing strategies. On the other hand, brand image is also known as consumer perceptions of brands that can influence their purchasing behavior. This study uses a quantitative approach method and data were collected through a survey of 113 respondents who are active social media users and have knowledge about Salted Egg Milea products. Data analysis techniques use Structural Equation Modeling (SEM) to test the relationship between the variables studied. The results of the study indicate that User Generated Content has a positive and significant influence on purchase intention of Salted Egg Milea products. In addition, brand image is also proven to have a positive and significant influence on purchase intention. The managerial implications of these findings are the importance of utilizing UGC and building a strong brand image to increase consumer purchase intention towards Salted Egg Milea products. This study contributes to the understanding of the influence of these factors in the context of marketing food and beverage products, especially salted egg products.